Role of Chief Executive Officers in Takeover Resistance: Effects of CEO Incentives and Individual Characteristics - Buchholtz, Ann K.; Ribbens, Barbara A. (Academy of Management Journal, 1994)
This study examined the influence of chief executive officers' (CEO) incentives and individual characteristics on the likelihood that target firms will resist takeover attempts. Results showed that...